Pembiayaan Pendidikan: Suatu Kajian Teoritis - Ferdi W. P (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2013)
The purpose of this analysis are to: 1) determine the factors that influence the cost of education, 2) identify the types of costs of education, and 3) recommend education funding model which is more effective and efficient. The study was conducted with a descriptive analysis of the documents relating to the cost of education. The results of this analysis are: 1) The factors that influence the cost of education, among others: a) rising prices, b) changes in teacherâ€™s sallaries; c) changes in population and increase in the percentage of children in public schools; d) increasing educational standards; e) the increasing age of children who leave school; f) the increasing demand for higher education; g) the existence of openness, participation, accountability in education from the planning, implementation and monitoring, and h) no financing models that can be used as a reference in the operationalization of the cost of education; 2) Identified the types of educational expenses include: a) direct costs; b) indirect cost; c) private cost; d) social cost; e) monetary cost; andÂ f) non monetary cost; 3) The education funding model which has more effective and efficient is human capital model/approach where aspects of financing can affect the productivity level which then affects the level of income of a person or group may ultimately contribute to the pace of economic growth and development.ABSTRAKÂ Tujuan kajian ini dimaksudkan untuk mengidentifikasi:1) faktor-faktor yang mempengaruhi biaya pendidikan; 2) jenis biaya pendidikan; dan 3) model pembiayaan pendidikan yang efektif dan efisien. Kajian ini dilakukan dengan melakukan analisis deskriptif terhadap dokumen-dokumen yang berhubungan dengan biaya pendidikan. Hasil kajian menunjukkan bahwa: 1) faktor-faktor yang mempengaruhi biaya pendidikan, antara lain: a) kenaikan harga; b) perubahan gaji guru; c) perubahan populasi dan kenaikan prosentasi anak di sekolah negeri; d) meningkatnya standar pendidikan; e) meningkatnya usia anak yang meninggalkan sekolah; f) meningkatnya tuntutan terhadap pendidikan lebih tinggi; g) adanya keterbukaan, partisipasi, akuntabilitas dalam penyelenggaraan pendidikan mulai dari perencanaan, pelaksanaan dan pengawasan; dan h) belum ada model pembiayaan yang dapat dipergunakan sebagai acuan dalam operasionalisasi biaya pendidikan; 2) jenis-jenis biaya pendidikan meliputi: a) biaya langsung; b) biaya tidak langsung); c) biaya pribadi; d) biaya masyarakat; e) monetary cost; dan f) non monetery cost; dan 3) model pembiayaan pendidikan yang efektif dan efisien yaitu model human capital di mana aspek pembiayaan dapat mempengaruhi taraf produktivitas yang dapat mempengaruhi taraf pendapatan seseorang atau kelompok sehingga pada akhirnya dapat berkontribusi terhadap kecepatan pertumbuhan ekonomi dan pembangunan.